Immune Cell Targets of Infection at the Tick-Skin Interface during Powassan Virus Transmission - Hermance, Meghan E. (PLoS One, 2016)
Powassan virus (POWV) is a tick-borne flavivirus that can result in a severe neuroinvasive disease with 50% of survivors displaying long-term neurological sequelae. Human POWV cases have been documented in Canada, the United States, and Russia. Although the number of reported POWV human cases has increased in the past fifteen years, POWV remains one of the less studied human pathogenic flaviviruses. Ixodes ticks are the vectors for POWV, and the virus is transmitted to a host’s skin very early during the tick feeding process. Central to the successful transmission of a tick-borne pathogen are complex interactions between the host immune response and early tick-mediated immunomodulation, all of which initially occur at the skin interface. In our prior work, we examined the cutaneous immune gene expression during the early stages of POWV-infected Ixodes scapularis feeding. The present study serves to further investigate the skin interface by identifying early cell targets of infection at the POWV-infected tick feeding site. An in vivo infection model consisting of POWV-infected ticks feeding on mice for short durations was used in this study. Skin biopsies from the tick feeding sites were harvested at various early time points, enabling us to examine the skin histopathology and detect POWV viral antigen in immune cells present at the tick feeding site. The histopathology from the present study demonstrates that neutrophil and mononuclear cell infiltrates are recruited earlier to the feeding site of a POWV-infected tick versus an uninfected tick. This is the first report demonstrating that macrophages and fibroblasts contain POWV antigens, which suggests that they are early cellular targets of infection at the tick feeding site. These data provide key insights towards defining the complex interactions between the host immune response and early tick-mediated immunomodulation.